Electronic Word of Mouth (EWOM) and Impulse Buying Affect Purchasing Decisions on Game Items - Kurniawan, Helmi Faiz; Setiawan, Alim; Musthofa, Musthofa (Devotion : Journal of Research and Community Service, 2023)
This study aims to explain whether there is an influence from Electronic Word of Mouth (EWOM) and impulse buying on purchasing decisions, and knowing whether income will affect impulse buying or not. This study uses an analytical descriptive basic method, in other words, the data collected in accordance with the actual state. This research was conducted through an application called Discord. The sample in this study used probability sampling techniques with sample sampling techniques. The sample that had been obtained in this study was 326 respondents. The data collection technique chosen is through the interview method using a questionnaire. Questionnaire testing through its validity and reliability test. Analysis of the data used in this study is the Structural Equation Model (SEM) method with an alternative method of Partial Least Square (PLS). The results showed that: (1) Ewom has a positive effect on purchasing decisions. (2) Impulse buying has no positive effect on purchasing decisions. (3) Purchasing ability has a positive effect on impulse purchasing decision. (4) purchasing ability has a positive effect on impulse buying. (5) Ewom has a positive effect on impulse buying.